1995
DOI: 10.1073/pnas.92.3.880
|View full text |Cite
|
Sign up to set email alerts
|

Dark-light: model for nightblindness from the human rhodopsin Gly-90-->Asp mutation.

Abstract: MATERIALS AND METHODSElectroretinography. Corneal electroretinograms (ERGs) were elicited by full-field 10-gs xenon photostrobe flashes and recorded at 0.1-1000 Hz by using methods and control values presented previously (6). Molecular Biology. Genomic DNA was isolated from peripheral blood samples. The Gly9OAsp mutation was found by sequencing the entire rhodopsin coding region, with target DNA generated by PCR amplification (7) of genomic DNA during 40 rounds of thermal cycling [94°C for 90 s, 54°C for 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
139
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(149 citation statements)
references
References 21 publications
9
139
1
Order By: Relevance
“…Such a mechanism is likely the cause for some forms of congenital night blindness. For example, the G90D rhodopsin mutant (26) opsin is constitutively active (27). A rod containing G90D rhodopsin seems to have a significant amount of apoprotein present in the dark (28), and its phenotype is that they appear as if they were light-adapted in the dark (26,29).…”
Section: Discussionmentioning
confidence: 99%
“…Such a mechanism is likely the cause for some forms of congenital night blindness. For example, the G90D rhodopsin mutant (26) opsin is constitutively active (27). A rod containing G90D rhodopsin seems to have a significant amount of apoprotein present in the dark (28), and its phenotype is that they appear as if they were light-adapted in the dark (26,29).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it has been shown that constitutive activity is not the cause of photoreceptor degeneration in transgenic mice carrying RP mutations (20). An alternative mechanism, involving thermal instability of the mutant rhodopsins, has also been proposed for CNB mutations, like G90D (12,13). Thus, different molecular mechanisms underlying RP and CNB have been outlined previously (34).…”
Section: Purification and Spectral Properties Of Thr-94 Rhodopsinmentioning
confidence: 99%
“…Another possible explanation for the observed G90D mutant phenotype has been proposed, i.e. enhanced rate of thermal isomerization due to lowered activation energy caused by the mutation (12,13). More recently, a third mutation associated with CNB, T94I, in the second transmembrane helix of rhodopsin, has been described (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas autosomal dominant (Ad) and autosomal recessive (Ar) RP are progressive disorders, congenital stationary night blindness is a nonprogressive disorder (9). Moreover, affected members of a speci c kindred having lifelong night blindness and carrying the rhodopsin mutation (G90D) show preservation of rod functions (10). In addition, how any of the gene defects (mutation) leads to photoreceptor death rather than functional impairment of the cell, as is observed in the case of color blindness, is not known.…”
Section: Genetic Contributionsmentioning
confidence: 99%